IMPLEMENTATION OF EMPOWERING THE POOR TO IMPROVE RURAL ECONOMY IN BOJO VILLAGE, MALLUSETASI DISTRICT, BARRU REGENCY - Asriani Asriani (Sean Institute, 2022)
This study aims to determine: How to implement empowering the poor to improve the rural economy in Bojo Village, Mallusetasi District, Barru Regency and to determine the supporting and inhibiting factors. The method used is qualitative and the data is obtained by means of observation, interview, documentation.The results of this study indicate that the implementation empowering the poor to improve the rural economy in Bojo village is carrying out activities by providing house repair assistance (house renovation), assistance to fishermen in the form of boat engine distribution, assistance to farmer groups in the form of seeds, BLT assistance. , business capital loan assistance managed by BUMDES, in the form of assistance to fulfill the nutrition of pregnant women and toilets, then the supporting factors, namely the existence of village funds, assistance that is right on target while the inhibiting factor is inadequate facilities and infrastructure.